Infant and Young Child Feeding Practices in Tanzania: The Impact of Mass Media and Interpersonal Communication. (7th June 2021) - Mulokozi, Generose; Beckstead, Emmalene; Jensen, Mindy; Baldauf, Megan; Smith, Jenna; Dearden, Kirk; Masau, Benesta Titus; Torres, Scott; Linehan, Mary; Glenn, Jeffrey; Hall, P. Cougar; West, Josh; et al.
Abstract: Objectives: We tested the hypothesis that mothers of infants < 2 y of age exposed to nutrition and health-focused radio and TV spots (M), interpersonal counselling (IPC), or both (M + IPC) were more likely than mothers with no exposure to media nor IPC to initiate breastfeeding in the first hour of life, breastfeed exclusively, introduce foods and liquids in addition to breastmilk at 6 mo, and feed the child a minimally acceptable diet. Methods: Between 2016 and 2020, the Addressing Stunting in Tanzania Early (ASTUTE) project conducted a behavior change intervention in the Lake zone of Tanzania that reached 4.4 million individuals through radio and TV spots, 6.4 million through community health worker home visits, 411, 000 through support groups, and 1.6 million through health facility-based counselling. We administered a cross-sectional survey to 5, 000 households with children < 2 y beforethe intervention and 5, 000 households after program activities ended. We used bivariate analyses and logistic regression to test our hypotheses. Results: Mothers exposed to M, IPC, or M + IPC were no more likely than mothers with no program exposure to breastfeed early (OR M = 0.8; IPC = 0.8; MIPC = 1.1) nor exclusively (OR M = 1.0; IPC = 0.9; M + IPC = 0.6). Program exposure was not associated with timely introduction of complementary foods but children of IPC mothers were significantly more likely to achieve minimum meal frequency (OR = 1.2, 95% CI = 1.0, 1.4) and children of IPC and M + IPC mothers were significantly more likely to achieve minimum dietary diversity (OR = 1.4, 95% CI = 1.2, 1.6; OR = 1.8, 95% CI = 1.5, 2.3). They were also more likely to be fed a minimally acceptable diet (OR for IPC = 1.5 95% CI = 1.2, 1.8; OR for M + IPC = 1.5, 95% CI = 1.2, 2.0). Adjusting for maternal age, education, and wealth attenuated our results. In separate analyses, in four of ASTUTE's five regions, reductions in stunting were 34.0% to 257.4% greater than the national average. Conclusions: Exposure to mass media and IPC was not associated with breastfeeding but IPC and M + IPC children were significantly more likely than children of unexposed mothers to eat a minimally acceptable diet. In this context, program planners may wish to focus on IPC as a cost-effective approach for improving complementary feeding. Funding Sources: ASTUTE was funded by UKAid (contract # PO 6803).